2015
DOI: 10.1016/j.artres.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of pulse wave imaging using conventional ultrasound in canine aortas ex vivo and normal human arteries in vivo

Abstract: The propagation behavior of the arterial pulse wave may provide valuable diagnostic information for cardiovascular pathology. Pulse Wave Imaging (PWI) is a noninvasive, ultrasound imaging-based technique capable of mapping multiple wall motion waveforms along a short arterial segment over a single cardiac cycle, allowing for the regional pulse wave velocity (PWV) and propagation uniformity to be evaluated. The purpose of this study was to improve the clinical utility of PWI using a conventional ultrasound syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The 50% upstroke was defined as the time-point, at which v PWI was closest in value to the average between the foot and the peak of the v PWI at each beam location. The choice of this tracking feature is justified because the early wavefront is less affected by the generated reflected waves [2] and also because previous studies have shown that it is the most robust compared to alternative tracking features (foot, 25% upstroke, 75% upstroke) [23]. In the case of the phantom, the initial pulse wave corresponds to a drop in pressure so the 50% downstroke was used as the tracking feature and was defined as the average between the foot and the negative peak of the v PWI .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 50% upstroke was defined as the time-point, at which v PWI was closest in value to the average between the foot and the peak of the v PWI at each beam location. The choice of this tracking feature is justified because the early wavefront is less affected by the generated reflected waves [2] and also because previous studies have shown that it is the most robust compared to alternative tracking features (foot, 25% upstroke, 75% upstroke) [23]. In the case of the phantom, the initial pulse wave corresponds to a drop in pressure so the 50% downstroke was used as the tracking feature and was defined as the average between the foot and the negative peak of the v PWI .…”
Section: Methodsmentioning
confidence: 99%
“… Regional and piecewise PWV values : Comparison to static testing derived values in the case of the phantom and evaluation of repeatability and agreement between regional and mean piecewise PWVs in the case of the healthy volunteers. Coefficient of determination (r 2 ) : Comparison of r 2 values for different parameter configurations provides a quality metric contingent upon both varying image SNR as well as frame rate [23]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transducer was positioned so that the pulse wave propagated in the opposite direction to the beam sweeping, and the time delay of each line was compensated for during post processing (Li et al 2015). RF signals were collected in 1 s acquisitions and digitized at 20 MHz which covered 3–4 pulses of the peristaltic pump.…”
Section: Ultrasound Pulse Wave Imagingmentioning
confidence: 99%